THE PROMOTION OF NATIONAL IDENTITY AND ROMANIAN TRADITIONAL AESTHETICS THROUGH THE USE OF CONTEMPORARY ADORNMENTS - MAȚCAN-LÎSENCO, Inga (Journal of Social Sciences)
This study accentuates the importance of the contemporary jewelry in the promotion of the national Bessarabanian identity. Romanian jewelry and adornments can include traditional elements, materials and techniques for the purpose of creating a unique masterpiece, which reflect Romanian culture. The ways through which contemporary jewerly can help promote Romanian national and traditional identity include inspiring traditional motifs, exploring cultural symbols, education and awareness, collaborating with local designers, and promoting sustainability. This study highlights the vital role of contemporary jewelry in preserving and transmitting Romanian Cultural Values in Bessarabia to future generations and in creating deep connections between artists, designers and the local community. It also highlights the importance of national identity in the development of contemporary jewelry, which can contribute to the promotion of Romanian traditions and crafts in the contemporary global context.